The Use of Image Media in Indonesian Language Learning to Improve Reading Skills in Elementary Schools - Riska Kurniati; Eny Munisah; Sumarno (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Students' reading ability still faces obstacles such as low reading interest and less interesting learning methods. This study uses a literature review to analyse the use of image media in Indonesian language learning to improve reading skills in elementary schools. The method used in this study is a systematic literature review using data accessed from Google Scholar. The research applied in this analysis consists of articles published from 2020-2024. For the initial search based on keywords, we found as many as 11,700 documents using the keyword "use of image media" in the Google Scholar database, then limited the search to the period 2020-2024, obtained as many as 7,150 documents, added again the keyword "Bahasa Indonesia" got 3,750 documents, then added again the keyword "reading ability" got 973 documents, and added the last keyword namely "elementary school" got 855 documents. Then, from the total number of 855 documents, only 10 were selected for further review by the researcher. Based on the research analysis, it was concluded that the use of visual media has proven effective in the learning process, particularly in Indonesian language learning at the elementary school level. Therefore, teachers are advised to use visual media in teaching and learning, as it is highly effective and makes learning much more enjoyable.